Pelecehan Seksual Terhadap Anak Dibawah Umur (Studi Kasus Pada Korban “X” Di Kecamatan Bandar Petalangan, Kabupaten Pelalawan) - Sartika Purnama Sari, Robi; Novarizal, Riky (SISI LAIN REALITA, 2022)
In general this study aims to provide an overview of the impact of sexual harassment on minors in the Bandar Petalangan District. Pelalawan District. Sex is an experienced part of human life. God created humans with sex and created sex in maintaining the continuity of human existence. However, sometimes there are some people. Experience the wrong sexual orientation so that the outlet for their sexual needs tends to abouse and even torture children. This paper will find out the effects of sexiual abouse on minors. This research uses qualitative research method with descriptive type. Which explains the effects of sexual harassment on minors that will be raised by the author in this discussion is traumatic Sexualization, Betrayal, feeling helpless, stigmazation